TGF-β Concentration in Breast Milk is Associated With the Development of Eczema in Infants - Morita, Yoshinori; Campos-Alberto, Eduardo; Yamaide, Fumiya; Nakano, Taiji; Ohnisi, Hidenori; Kawamoto, Minako; Kawamoto, Norio; Matsui, Eiko; Kondo, Naomi; Kohno, Yoichi; Shimojo, Naoki (Frontiers in Pediatrics, 2018)
Background: Transforming growth factor (TGF)-β in breast milk is crucial for mucosal immune system in the neonatal period. We hypothesized that the level of exposure to TGF-β from breast milk in the first month of life is related to the development of eczema later in life. Thus, the present study investigated whether changes in TGF-β levels between colostrum and mature milk are associated with such occurrence in a birth cohort study. Methods: Colostrum and 1-month breast milk samples were collected from mothers who participated in our birth cohort study. TGF-β1 and TGF-β2 levels in breast milk were measured using a commercial ELISA kit. The development of eczema in the first 6 months after birth was assessed based on parent's response to a questionnaire. Levels of TGF-β1 and TGF-β2 were compared in breast milk from mothers of infants with and without eczema. Results: In children with eczema, TGF-β1 levels were higher in colostrum, but lower in 1-month milk. A lower TGF-β1 ratio (1-month milk/colostrum) was related to the development of eczema during the first 6 months of life. There was no difference in TGF-β2 ratio (1-month milk/colostrum) between eczema group and control group. Conclusions: Concentration of TGF-β1 but not TGF-β2 in breast milk during the first month after birth may be associated with eczema later in life. Factors that increase TGF-β1 levels in breast milk may play a role in preventing allergic disease.